Age determination and benthic foraminifera abundance of an onshore sediment core from the Miaodao stratigraphic section (MDS) in the northwest region of the Miaodao Archipelago in the Bohai Sea - Shuhuan Du; Baosheng Li; Muhong Chen; Rong Xiang; Donefeng Niu; Yuejun Si (PANGAEA, 2017)
Reconstruction of the generation, development, and evolution of modern storms through paleotempestology is used to understand the regularity of storm activity and the relationship between storm activity and global climate change. Existing paleotempestology research in China is concentrated mainly on the low latitude sediments deposited since the Holocene (about 7000 a). In this study, we examine the storm deposits in the eolian sediments of the Bohai Sea coastal zone at middle latitudes, choosing the Miaodao stratigraphic section (MDS) as the target area. This area is located in the Bohai Sea strait and shows evidence of storms since the last interglacial period using an analysis of the grain size parameter, element ratios, and marine micropaleontology foraminifera fossils in the sediment during the last 130 ka that can be used in our paleotempestology research. The results include three main findings: (1) the marine micropaleontology foraminifer fossils appear in the eolian sediment of the MDS and, in combination with grain size parameter and element ratios of the sediments, serve as evidence of the paleotempestology record on the Bohai Sea coastal zone; (2) planktonic foraminifera fossils appear in the MDS, indicating that the Yellow Sea warm current affected the Bohai Sea during the last interglacial period; and (3) storm activity in the marine isotope stage (MIS) 5a has been recorded in the MDS 15 times. The findings of this study expand the paleotempestology record from 7000 a to 90 ka and serve as a reference for research for middle latitude storm activity.
Supplement to: Du, S et al. (2016): Paleotempestology evidence recorded by eolian deposition in the Bohai Sea coastal zone during the last interglacial period. Marine Geology, 379, 78-83, https://doi.org/10.1016/j.margeo.2016.05.013